De la porte de Brandebourg à La Havane : Wilder, Hitchcock et l’héritage révolutionnaire - Julie Michot (Transatlantica)
Billy Wilder’s One, Two, Three (1961) and Alfred Hitchcock’s Topaz (1969) were not successful when released. This essay argues that in spite of this lack of critical acclaim, they are worth revisiting today: their respective plots—the former, farcical, the latter, rather nebulous—dissimulate subtle ideological stances all the more unexpected because neither Wilder nor Hitchcock were known for making their political views public. The aim of this essay is to study the devices used by both whether in their script or filming, to illustrate their vision of capitalism and communism. The two directors did criticize the revolutionary heritage—but in the midst of the Cold War, they also took an unsupportive attitude towards the proposed model of their adopted country.